Semiotic Analysis of the 7-Month "Mitoni" Ritual in Javanese Tradition - Tanzela, Salsabila Izza; Evianty, Rina (Asian Journal of Applied Education (AJAE), 2025)
The title of this thesis is "Semiotic Analysis of the 7-Month "Mitoni" Ritual in the Javanese Tradition". The purpose of this study is to analyze the meaning of the Mitoni ceremony in the seventh month of pregnancy in the Javanese tradition and to explain the symbols that occur in this tradition to the people of Sei Buluh Village, Teluk Mengkudu District, Serdang Bedagai prefecture. This study uses a descriptive-qualitative method, with the research location in Darul Aman Hamlet, Sei Buluh Village. The data will be analyzed using Charles Sanders Peirce's semiotic theory, which includes the study of icons, indexes, and symbols in the Mitoni tradition. This research shows that the Mitoni tradition has a deep spiritual meaning. It serves as a prayer, motivation and hope for the family and society for pregnant women and their unborn children.